2017
DOI: 10.1186/s13075-017-1435-5
|View full text |Cite
|
Sign up to set email alerts
|

Behçet’s disease risk association fine-mapped on the IL23R–IL12RB2 intergenic region in Koreans

Abstract: BackgroundBehçet’s disease (BD) susceptibility had been associated with single-nucleotide polymorphisms (SNPs) in IL23R–IL12RB2, IL10, STAT4, or ERAP1 locus in Japanese, Turkish, Chinese, and other populations, but not in a Korean genome-wide association study (GWAS). We aimed to fine-map BD risk association of these four loci using extensive imputation and additional genotyping for replication.MethodsIn the discovery phase, 369 patients with BD enrolled in the previous Korean GWAS and 2000 controls retrieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 17 publications
3
13
0
1
Order By: Relevance
“…A significant association (reaching a GWAS p value) of the IL-23R gene with BD was found at the SNP rs11209026 (Gly149Arg) in Japanese, and at the SNP rs76418789 (Arg381Gln) in Turkish cohort [61]. The association between BD and the IL-23R/IL-12RB2 genes appeared to be consistent in multiple reports with different populations including Turkey [52], Japanese [53], Han Chinese [62,63], Iranian [64], Western Algeria [65], and Korean [66].…”
Section: Il-12a Il-23r and Il-12rb2supporting
confidence: 79%
See 1 more Smart Citation
“…A significant association (reaching a GWAS p value) of the IL-23R gene with BD was found at the SNP rs11209026 (Gly149Arg) in Japanese, and at the SNP rs76418789 (Arg381Gln) in Turkish cohort [61]. The association between BD and the IL-23R/IL-12RB2 genes appeared to be consistent in multiple reports with different populations including Turkey [52], Japanese [53], Han Chinese [62,63], Iranian [64], Western Algeria [65], and Korean [66].…”
Section: Il-12a Il-23r and Il-12rb2supporting
confidence: 79%
“…The associations of the TLR4 gene with BD are conflict in different reports. It was found in Japanese [91], Korea [92] and Turkish cohorts [66], but not in Italian [93], Tunisian [94], and Chinese cohorts [95]. Of note, two BD protective TLR4 variants identified in the Turkish cohort, p.Asp299Gly (rs4986790) and p.Thr399Ile (rs4986791) were associated with hyporesponsiveness to endotoxin [96].…”
Section: Tlr2 and Tlr4mentioning
confidence: 99%
“…Recently, several different genetic studies have also identified non-HLA variants with biological meaning (e.g., IL10, IL23RIL12RB2) [10,11]. A GWAS has recently shown that the Endoplasmic Reticulum Aminopeptidase Protein 1 (ERAP1) gene is associated with BS, and that ERAP1 is epistatic with HLA-B*51 allele [11].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Recently, several different genetic studies have also identified non-HLA variants with biological meaning (e.g., IL10, IL23RIL12RB2) [10,11]. A GWAS has recently shown that the Endoplasmic Reticulum Aminopeptidase Protein 1 (ERAP1) gene is associated with BS, and that ERAP1 is epistatic with HLA-B*51 allele [11]. Interestingly, ERAP1 encodes for a molecule in the endoplasmic reticulum that cuts the N-terminal amino acids from epitope precursors for HLA class I presentation [10,12,13].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…The GWAS identified the IL-23R SNP rs11209026 (Gly149Arg) in association with the Japanese cohort, and SNP rs76418789 (Arg381Gln) with the Turkish population [ 65 ]. In addition, the IL-23R/IL-12RB2 genes with multiple SNPs (rs1495965, rs924080 rs11209032, rs17375018, rs7517847, 10489629 and rs1966176) were associated with BD in the cohorts of Turkey [ 56 ], Japanese [ 57 ], Han Chinese [ 66 , 67 ], Iranian [ 68 ], Western Algeria [ 69 ] and Korean [ 70 ].…”
Section: Multiple Interleukins (Il) Family Genes Are Involved In Suscmentioning
confidence: 99%